Kebijakan Pembatasan Kepemilikan Tanah Non-Pertanian oleh Perorangan Untuk Menyelesaikan Ketimpangan Kepemilikan Tanah yang Berkeadilan: Policy for Restricting Non-Agricultural Land Ownership by Individuals to Resolve Inequalities in Fair Land Ownership - Silviana, Ana; Emha, Zidney Ilma Fazaada (Warkat, 2021)
Until now there are no regulations governing the maximum limit of land ownership, especially non-agricultural, so that there is increasing inequality in land ownership. This research aims to determine and analyze the causes of inequality in land ownership and the policies implemented in setting maximum limits on non-agricultural land ownership for individuals. The method used is socio-legal research, namely a legal research method that attempts to see the law in a real sense or examine how the law works in society. Research data was taken from field research with official sources within the Central Java BPN Regional Office, Semarang City and Semarang Regency Land Offices as well as literature study research using legal materials, which were then analyzed qualitatively using inductive methods. The results show that inequality in land ownership will continue to occur as long as there is no legal certainty governing non-agricultural land ownership limits, so far it has only been in the form of internal administrative regulations. In order to realize a land policy for social welfare and justice, it is necessary to immediately issue regulations regarding restrictions on non-agricultural land ownership in the form of a law.